UJI KUALITATIF KANDUNGAN BORAKS PADA BAKSO IKAN BAKAR JAJANAN KAKI LIMA MENGGUNAKAN BAHAN ALAMI KUNYIT DI KOTA TANJUNGPINANG - Weni Enjelina; Aura Vionalita; Samosir, Kholilah (Jurnal Sanitasi Profesional Indonesia, 2024)
Grilled fish meatballs are snacks that are very popular with people from small children to adults in Tanjungpinang City. Grilled fish balls have a low shelf life, so it is feared that there will still be the use of harmful preservatives such as borax to prolong the shelf life of meatballs. Borax can cause disturbances in the central nervous system, kidney and liver function. The purpose of this study was to qualitatively determine the borax content in grilled fish balls for street food using natural ingredients turmeric in Tanjungpinang City. The type of research used is descriptive qualitative by using an observational research design and conducting 2 tests, namely the turmeric toothpick test and the turmeric extract test. The number of samples in this study were 25 grilled fish ball traders, 3 samples of grilled fish balls were taken to be tested from 25 traders, totaling 75 samples. The results of the validation test before checking the borax content with turmeric toothpicks and turmeric extract that were given borax at a concentration of 10% there was a color change and the examination of the borax content in grilled fish balls with a toothpick test of turmeric and turmeric extract the results obtained that there was no borax content in the sample indicated that there was no color change. Suggestions in this study are that it is expected to continue the research by testing the validation of the turmeric toothpick test tool and turmeric extract on borax with a small concentration of less than 10% and conducting a hygiene and sanitation inspection of making grilled fish balls at traders.